"Melismas medievales" en Concierto Barroco: enumeración y artificiosidad de Alejo Carpentier. Issue 3 (2nd July 2016) - Duque, Adriano
ABSTRACT: The distinction between condensation, proliferation, and substitution defines, according to Severo Sarduy, the tenets of the Latin American neobarroque movement. This article, though sympathetic to the ideas of Sarduy, aims at clarifying the terms in which Alejo Carpentier conducts a recreation and evocation of the baroque movement in Europe and America. Taking Leo Spitzer's definition of chaotic enumeration as a focal point, it aims to clarify the mechanisms of literary composition in Carpentier. It argues that Carpentier's vision relies on an absolute yet universal and inclusive role of America in the shaping of the modern world.